The Microvascular and Macrovascular Benefits of Fibrates in Diabetes and the Metabolic Syndrome: A review - Malur, Pavan (Mo Med, 2017)
BACKGROUND: The purpose of this article is to discuss the evidence regarding potential macrovascular and microvascular benefits of fibrate therapy in general and fenofibrate specifically. METHODS: We performed a literature review summarizing the results of studies testing fibrates on relevant. RESULTS: Although statins are the first line therapy with an unparalleled amount of evidence for reducing the risk of cardiovascular disease (CVD) in patients with dyslipidemia and the metabolic syndrome (MetS), there are several landmark studies that have focused on the potential benefits of fibrate therapy for reducing CVD risk. Fibrates confer benefits mostly for patients with diabetes mellitus (DM), MetS, and atherogenic dyslipidemia. Recently, many studies have shown that fibrates confer benefits on the vascular system as well as the liver and kidneys. Fibrates also have demonstrable benefits in cohorts of patients with DM and renal disease. CONCLUSIONS: Fibrates appear to provide significant microvascular and macrovascular benefits particularly in patients with DM, MetS, or renal disease.